A Comparison of SIEA/SCIA and DIEP Flaps for Autologous Breast Reconstruction - Somers, Sydney; Foley, Brittany; Dadzie, Aaron; Hart, Chase; Chen, Joanna; Bautista, Catherine H.; Scott, Kaylee; Eddington, Devin; Agarwal, Jayant P.; Kwok, Alvin C. (Journal of Reconstructive Microsurgery, 2025)
Background The deep inferior epigastric perforator (DIEP) flap is considered the gold standard for autologous breast reconstruction (ABR). Less commonly used abdominal flaps include the superficial inferior epigastric artery (SIEA) and the superficial circumflex iliac artery (SCIA) flaps which are based on the superficial vasculature of the abdominal wall. We sought to compare complication rates between DIEP and superficial system flaps and their associated risk factors.Methods A retrospective chart review of 400 breast cancer patients undergoing abdominally-based free flap breast reconstruction with either a DIEP or superficial flap from January 2017 to December 2023 was performed at a single institution. The primary outcome was breast and abdominal site complications.Results A total of 638 flaps, 571 (89.4%) DIEP and 67 (10.5%) superficial, were performed with flap complication rates of 27.3 and 22.4%, respectively. At the recipient site, there was a significant difference in the rate of postoperative thrombosis (0.7% vs. 4.5%, p = 0.015); however, there were no differences for flap failure (0.4% vs. 1.5%, p = 0.28) or other flap complications. Donor site outcomes were similar between groups. Although not statistically significant, abdominal bulging was seen in 18 DIEP flap patients compared with none observed in the superficial flap patients (p = 0.24). When controlling for age, BMI, and radiation history, the overall rate of superficial flap and abdominal complications was not statistically significant from the rate of DIEP flap complications (p = 0.576).Conclusion Compared with DIEP flaps, superficial flaps had significantly higher rates of immediate perioperative thrombosis. However, there were no significant differences in rates of flap failure or other flap complications with superficial flaps compared with DIEP flaps. There was a clinically significant trend toward increased abdominal bulging with the use of DIEP flaps. Our results will help surgeons better understand the risks and benefits associated with superficial flaps for ABR.
Keywords: SIEA; DIEP; flap failure